The effect of technology autonomy and algorithm aversion on perceived uncertainty in purchase decisions in e-commerce - Tiok Jia Fen; Mutty Claudia Dewinda (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The increasing adoption of artificial intelligence (AI) technologies in e-commerce has transformed consumer decision-making processes, raising important questions regarding consumer trust and perceptions of algorithm-driven systems. This study investigates the effects of Technology Autonomy and Algorithm Aversion on Perceived Uncertainty and examines the mediating role of Perceived Uncertainty in influencing Purchase Decisions among Indonesian e-commerce users. Employing a quantitative research design, data were collected through a survey of 140 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that Technology Autonomy significantly reduces Perceived Uncertainty, indicating that consumers are more comfortable with autonomous technologies when they are perceived as reliable and beneficial. Conversely, Algorithm Aversion significantly increases Perceived Uncertainty, reflecting consumers’ skepticism toward algorithm-based recommendations and decision-making systems. However, Perceived Uncertainty does not significantly influence Purchase Decisions and fails to mediate the relationships between Technology Autonomy, Algorithm Aversion, and Purchase Decisions. These results suggest that although consumers’ perceptions of AI technologies shape their levels of uncertainty, such perceptions are insufficient to directly determine purchasing behavior in the Indonesian e-commerce context. The study contributes to the emerging literature on consumer behavior and AI adoption by highlighting the limited explanatory role of perceived uncertainty in online purchase decisions and underscores the need to consider other psychological and contextual factors influencing consumer acceptance of algorithm-driven technologies. Keywords: Technology Autonomy; Algorithm Aversion; Perceived Uncertainty; Purchase Decision